The allosteric modulation of Complement C5 by knob domain peptides - Macpherson, A; Laabei, M; Ahdash, Z; Graewert, MA; Birtley, JR; Schulze, M-SE; Crennell, S; Robinson, SA; Holmes, B; Oleinikovas, V; Nilsson, PH; Snowden, J; et al. (eLife Sciences Publications, 2021)
Bovines have evolved a subset of antibodies with ultra-long CDRH3 regions that harbour cysteine-rich knob domains. To produce high affinity peptides, we previously isolated autonomous 3-6 kDa knob domains from bovine antibodies. Here, we show that binding of four knob domain peptides elicits a range of effects on the clinically validated drug target complement C5. Allosteric mechanisms predominated, with one peptide selectively inhibiting C5 cleavage by the alternative pathway C5 convertase, revealing a targetable mechanistic difference between the classical and alternative pathway C5 convertases. Taking a hybrid biophysical approach, we present C5-knob domain co-crystal structures and, by solution methods, observed allosteric effects propagating >50 Å from the binding sites. This study expands the therapeutic scope of C5, presents new inhibitors and introduces knob domains as new, low molecular weight antibody fragments, with therapeutic potential.